1994
DOI: 10.1084/jem.179.2.601
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella stimulate macrophage macropinocytosis and persist within spacious phagosomes.

Abstract: Light microscopic studies of phagocytosis showed that Salmonella typhimurium entered mouse macrophages enclosed in spacious phagosomes (SP). Viewed by time-lapse video microscopy, bone marrow-derived macrophages exposed to S. typhimurium displayed generalized plasma membrane ruffling and macropinocytosis. Phagosomes containing Salmonella were morphologically indistingnishable from macropinosomes. SP formation was observed after several methods of bacterial opsonization, although bacteria opsonized with specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
200
1
4

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 322 publications
(220 citation statements)
references
References 23 publications
15
200
1
4
Order By: Relevance
“…The reason for the difference in size between the vacuoles is currently unknown. Studies with other organisms such as Salmonella typhimurium have shown that this pathogen also lives inside large vacuoles [24]. It has been argued that large vacuoles, in contrast to tight vacuoles, are advantageous for the bacterium because they decrease the concentration of any intravacuolar bactericidal product delivery by the host cell.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for the difference in size between the vacuoles is currently unknown. Studies with other organisms such as Salmonella typhimurium have shown that this pathogen also lives inside large vacuoles [24]. It has been argued that large vacuoles, in contrast to tight vacuoles, are advantageous for the bacterium because they decrease the concentration of any intravacuolar bactericidal product delivery by the host cell.…”
Section: Discussionmentioning
confidence: 99%
“…Although SPI-1 gene expression might not be optimal under the growth conditions used, recent microarray data showed that SipB and other SPI-1 genes are transcribed in stationary phase (Adkins et al, 2006). Moreover, since the SPI-1 apparatus and plasma membrane ruffling are activated within 2 min of macrophage exposure to S. enterica serotype Typhimurium grown to stationary phase (Alpuche-Aranda et al, 1994), it is unlikely that our interpretation of the data was significantly affected by the experimental conditions used for the adhesion assays presented. Nevertheless, it remains possible that SPI-1 plays some role in Salmonella uptake in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Typhimurium, which causes typhoid in mice and diffuse enteritis and, less frequently, bacteraemia in humans, is able to survive in mouse macrophages and in human macrophages [200]. Furthermore, Typhi induces ruffling and micropinocitosis in murine macrophages, but internalization is followed by formation of fewer numbers of SP than Typhimurium, an indicator of reduced capability to survive within macrophages that is essential in pathogenesis [201,202]. However, the exact role of the survival of salmonella in macrophages is not known and is made more difficult to rationalize by the reported ability of salmonella to lyse macrophages both in itro and in i o [203][204][205].…”
Section: Extraintestinal Infection : Interaction With the Reticulo-enmentioning
confidence: 99%